Study on challenges application ground improvement and soil stabilization method in Sabah construction industry - Farahana Ahwil @ Kairin (2022)
The practice of ground improvement is commonly characterized as the use of mechanical means to remedy terrible ground conditions. Ground improvement techniques improve the treated soil parameters to satisfy project performance goals. Due to the scarcity of suitable development sites, ground improvement is a fast-developing profession. Engineers are confronted with a challenging problem in constructing structures on insufficient and poor locations. Therefore, it is necessary to investigate the challenges in the application of ground improvement and soil stabilization in Sabah construction industry. Questionnaire surveys with a total of 50 respondents were attained and analysed via BIM SPSS and Microsoft Excel software. The demographic data collected was tested by descriptive statistics frequencies analysis and transformed to bar charts, and pie chart for easy interpretation. The Chi-Square test was used to prove the significance between two variables which is the demographic data such as gender, age, and working period and the method that have been engaged by the respondents. From the analysis, there were significance of the age and working period with the other variables. The familiarity of the respondents was also assessed using the questionnaire survey. The challenges in application of ground improvement and soil stabilization were assessed using the RII analysis where it was found that cost was ranked first as the most significant challenge in the implementation, followed by air pollution, organic content, and stress history. From this research, we can have more knowledge in the implementation of the most used ground improvement method, identified the challenges in implementing the methods in Sabah construction industry and to aid research in geotechnical engineering to develop more method in improving ground that will have less challenges in its implementation.